2019
DOI: 10.1088/1757-899x/578/1/012060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial activity of sesquiterpene Ar- Turmerone from Curcuma soloensis Val. rhizomes

Abstract: Curcuma soloensis Val. is a family plant Zingiberaceae and is known as “temu glenyeh”. This plant has potential as a medicinal plant but has not been widely reported about its bioactivities. One of them was antibacterial activity. Therefore, the aim of this study was to evaluate the antibacterial activity of ar-turmerone, a sesquiterpenoid which was successfully isolated from Curcuma soloensis Val. rizhomes. Antibacterial test was carried out by using disc diffusion method and evaluated against four bacteria n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…This compound has also been found in Aglaia odorata Lour (Joycharat et al 2014). The growth inhibition test performed by others has revealed that artumerone has no or low inhibitory effect on E. coli growth (Lee 2006 andMarliyana et al, 2019), which may be due to its relatively lower concentration in their extract. Still other have determined that the essential oil of C. Longa and the extract of Jathyadi Thailam, both containing ar-tumerone and other compounds, possess antibacterial effect on MRSA (Mandrika et al, 2021 andSrisayam et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…This compound has also been found in Aglaia odorata Lour (Joycharat et al 2014). The growth inhibition test performed by others has revealed that artumerone has no or low inhibitory effect on E. coli growth (Lee 2006 andMarliyana et al, 2019), which may be due to its relatively lower concentration in their extract. Still other have determined that the essential oil of C. Longa and the extract of Jathyadi Thailam, both containing ar-tumerone and other compounds, possess antibacterial effect on MRSA (Mandrika et al, 2021 andSrisayam et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…These are DGEA2 reported by Padmavathi et al (2014) , DGEA8 by Beavers et al (2019) , Again, for the AC CEF, 2 out of total 7 compounds detected, were reported with antibacterial effects ( Table 4 ). These are DGAC6 by Marliyana et al (2019) and DGAC7 by Padmavathi et al (2014) .…”
Section: Discussionmentioning
confidence: 99%
“…Cho đến nay, hoạt tính kháng H. pylori của các hợp chất ar-turmerone, curzerene và zerumbone chưa được báo cáo. Ar-turmerone được chứng tỏ không có hoạt tính kháng khuẩn 70 trong khi curzerene và zerumbone biểu hiện hoạt tính kháng khuẩn phổ rộng đối với các loài vi khuẩn Gram âm và Gram dương 71,72 . Zerumbone cũng được chứng minh có tác động ức chế và làm suy giảm biofilm của các loài vi khuẩn S. aureus, E. coli, Pseudomonas aeruginosa và nấm Candida albicans 73 .…”
Section: Hiệu Suất Thu Tinh Dầuunclassified